Application of Multi-Sensors Information Fusion for Self-protection System of Robot - Qiuhong Gao (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
This paper developed a kind of robot self-protection system using the multi-sensors information fusion technology. This system used five groups of photoelectric sensor and ultrasonic sensor which were installed in different direction of the robot. In this study, signals were gathered by using the complement of ranging of photoelectric sensor and ultrasonic sensor. Then the signals were sent to MCU to achieve multi-sensors information fusion.Core fusion technology was the adaptive weighted fusion estimation algorithm, which can make measurement data more accurate. With such technology, an accurate robot self-protection command was made as to avoid obstacles, to judge narrow highland and to prevent dropping. The experiment results validated its good self-protection function. DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2312